2017
DOI: 10.4187/respcare.05344
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nebulizer Position on Aerosolized Epoprostenol Delivery in an Adult Lung Model

Abstract: The greatest amount of mean epoprostenol deposition resulted with the nebulizer placed at the humidifier inlet or outlet in a ventilator with bias flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Previous studies identified important factors that individually, and in combination, impact aerosol delivery, including the following: position in the ventilator circuit, [1][2][3][4] humidification, 2,[5][6][7][8] duty cycle, 6,7,9 bias flow, 1,5 nebulizer technology, 1,2,6,7,10,11 nebulizer driving pressure and flow, 5,12 internal ventilator valves, 13 device reliability, 14 fill volume, 4,15 and treatment time. 6,7 Output data from commercially available devices published in the literature, 1,2,5,8,[16][17][18][19][20][21] demonstrate that, with current technologies, dose delivery varies widely based on nebulizer technology and ventilator setting are summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified important factors that individually, and in combination, impact aerosol delivery, including the following: position in the ventilator circuit, [1][2][3][4] humidification, 2,[5][6][7][8] duty cycle, 6,7,9 bias flow, 1,5 nebulizer technology, 1,2,6,7,10,11 nebulizer driving pressure and flow, 5,12 internal ventilator valves, 13 device reliability, 14 fill volume, 4,15 and treatment time. 6,7 Output data from commercially available devices published in the literature, 1,2,5,8,[16][17][18][19][20][21] demonstrate that, with current technologies, dose delivery varies widely based on nebulizer technology and ventilator setting are summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The Anderson, et al, 9 study also reported nearly identical Mean Total Dose values for epoprostenol collected on the filter: 6,347 (±973) ng for the dry side versus 6,537 (±2,234) ng for the wet side of the humidifier. Based upon our Mass Balance data showing approximately 15% deposition in the humidifier due to dry side mounting, it could be expected that the Inhaled Mass for the Aerogen VMN would be higher with wet side mounting because no humidifier deposition would have occurred.…”
Section: Resultsmentioning
confidence: 81%
“…No maximum output rate is specified by the manufacturer although VMNs have been reported to function during continuous infusion aerosol delivery at output rates greater than 12 mL/h; e.g., 20.2 mL/h when pre-tested to ascertain maximum output. 9 While some Aerogen VMNs can apparently function reliably above 12 mL/h, knowing which would require clinicians to pre-test VMNs before use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations